2009
DOI: 10.1107/s1600536809019461
|View full text |Cite
|
Sign up to set email alerts
|

6-Amino-2,5-bis(pivaloylamino)pyrimidin-4(3H)-one dihydrate

Abstract: The asymmetric unit of the title compound, C14H23N5O3·2H2O, contains two crystallographically independent 6-amino-2,5-bis­(pivaloylamino)pyrimidin-4(3H)-one mol­ecules (A and B) with similar geometry and four water mol­ecules. In both independent mol­ecules, one of the amide groups is almost coplanar with the pyrimidine ring [dihedral angle of 12.85 (9) in A and 12.30 (10)° in B], whereas the other amide group is significantly twisted away from it [dihedral angle is 72.18 (7) in A and 71.29 (7)° in B]. In each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The result showed that the title compound was the byproduct of the reaction. The pyrimidinone ring is planar, as it is in a related compound (Fun et al, 2009). This is in contrast with another related compound (Shang et al, 2007), where the heterocyclic ring is twisted.…”
Section: Data Collectionmentioning
confidence: 86%
See 1 more Smart Citation
“…The result showed that the title compound was the byproduct of the reaction. The pyrimidinone ring is planar, as it is in a related compound (Fun et al, 2009). This is in contrast with another related compound (Shang et al, 2007), where the heterocyclic ring is twisted.…”
Section: Data Collectionmentioning
confidence: 86%
“…For background to raltegravir, see: Steigbigel et al (2008). For related structures, see: Shang & Shang (2007); Fun et al (2009). Mo K radiation = 0.11 mm À1 T = 113 K 0.20 Â 0.16 Â 0.12 mm…”
Section: Related Literaturementioning
confidence: 99%